1997
DOI: 10.1046/j.1469-0705.1997.09040248.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between two methods of standardization for gestational age differences in fetal nuchal translucency measurement in first‐trimester screening for trisomy 21

Abstract: Our purpose was to compare two different methods of expressing nuchal translucency (NT) measurements in first-trimester screening for trisomy 21: the difference in millimeters from the median of nuchal translucency (delta value: delta NT) and the multiple of the expected median (MoM). Fetal nuchal translucency was measured in 32 fetuses with trisomy 21 and in 3180 normal fetuses at 9-13 weeks' gestation. For each fetus, the measured nuchal translucency was expressed both as a delta value and MoM. The effective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
1
1

Year Published

1999
1999
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 0 publications
3
22
1
1
Order By: Relevance
“…Total congruency or high correlation between any two tests means that there is no advantage in performing both. Lack of correlation between NT and TT in normal pregnancies [14] and in cases with DS, found in the present study, validates the methodology of multiplication of the LRs [23,24] in order to obtain a meaningful integrated risk. Analysis of the extent of overlapping in our study showed that between 25 and 35 years there was an average overlapping of around 33% among the screen positive cases of DS.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Total congruency or high correlation between any two tests means that there is no advantage in performing both. Lack of correlation between NT and TT in normal pregnancies [14] and in cases with DS, found in the present study, validates the methodology of multiplication of the LRs [23,24] in order to obtain a meaningful integrated risk. Analysis of the extent of overlapping in our study showed that between 25 and 35 years there was an average overlapping of around 33% among the screen positive cases of DS.…”
Section: Discussionsupporting
confidence: 84%
“…The extent of overlapping between the tests was evaluated using age-adjusted calculations performed according to the methodology reported before [21][22][23]. The LRs of the tests were adjusted to specific age-derived background risks.…”
Section: Methodsmentioning
confidence: 99%
“…Based on studies involving a wider sample however [15,28,29] , the risk of chromosomal abnormalities was in the range of 7.49 and 9.57%. Our result was 8.3%, corresponding with these literature data.…”
Section: Discussionmentioning
confidence: 99%
“…In the first trimester, nuchal translucency (NT) is investigated, in which the distance between the external surface of the occipital bone and the internal surface of the skin is measured in a longitudinal section [6][7][8][9][10] , its proposed limit being 3 mm [11][12][13][14] . Some authors recommend the use of a multiple of median, compared to values measured at different weeks of normal pregnancies [15][16][17][18] .…”
Section: Nuchal Oedema In the First Trimestermentioning
confidence: 99%
“…Increased fetal nuchal translucency (NT) seems to be a well established ultrasonographic marker for aneuploidy screening, particularly when it is measured during the first trimester [1][2][3][4][5] . To date, NT screening combined with maternal age at early mid-trimester can identify about 75 -80% of chromosomal abnormalities with a false-positive rate of 5% 1,6 -8 .…”
Section: Introductionmentioning
confidence: 99%